Many Routes toward Trust: A Social Network Analysis of the Determinants of Interpersonal Trust - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2003)
This article presents a theoretical framework that identifies three aspects of a social relationship that are critical determinants of interpersonal trust, and examines the differentiated roles that these three aspects of a social relationship play in trust development. The study moves beyond the study of unidirectional trust formation in dyadic interpersonal relationships, which has dominated the current literature, to an exploration of reciprocated trust and social-structural routes toward trust. The framework is tested via a social network analysis of relationships among employees of a multi-departmental, white-collar work organization. Ultimately, it is aimed to enrich existing theoretical and empirical knowledge concerning the determinants of interpersonal trust and also bring a social network perspective into interpersonal trust research. The managerial implications of this study are twofold. First, the results should help managers understand how trust forms among their employees. As organizations shift toward more decentralized, laterally-controlled forms, informal trust networks represent an increasingly important determinant of organizational effectiveness. Understanding how trust networks form will enable managers to better harness the benefits of trust. Second, the theory and findings open a realm of possibilities to employees who want to be trusted but are unsure how to go about it.